Periosteal osteosarcoma: A case report (Medical Journal of Indonesia, 2003)
Periosteal osteosarcoma is a rare type of malignant bone neoplasm, with predominantly cartilaginous component and arising on the bone surface. Reports of the case in the literature were rare. Last case was reported by Mayo Clinic in 1999. We report a case of periosteal osteosarcoma in a 17-year-old male, who was treated surgically with a limb salvage procedure, neoadjuvant and adjuvant chemotherapy were also given to the patient. There was no local recurrence and lung metastases up to 14 months after surgery. (Med J Indones 2003; 12: 166-70)